EFEKTIFITAS PENDIDIKAN KESEHATAN PERTOLONGAN PERTAMA KECELAKAAN TERHADAP PENGETAHUAN TENTANG KERACUNAN MAKANAN DAN GAS KARBON MONOKSIDA (CO) SISWA KELAS XI - Candra Patniawati Candra Patniawati; Milkhatun; Alfi Ari Fakhrul Rizal; Zulmah Astuti; Ni Wayan Wiwin Asthiningsih (Open Edutech Indonesia, 2023)
Based on cases that illustrate the lack of information about the incidence of food poisoning and carbon monoxide (CO) gas that afflicts a person. Especially in students who often consume fast food snacks have a great risk of experiencing food poisoning and exposure to air pollution due to land transportation can endanger student health because it can cause carbon monoxide (CO) gas poisoning. The purpose of this activity is to increase students' knowledge through health education regarding accident first aid about food poisoning and carbon monoxide (CO) gas. This activity was carried out on grade XI students of Madrasah Aliyah Private Miftahul Ulum Anggana. As a result of this health education activity, students can understand how accident first aid is about food poisoning and carb-monoxide (CO) gas and students are able to answer questions given about the importance of providing accident first aid in such cases.